Moral Hazard Problem in Public Policymakers - Noor Alam (European Scientific Journal, ESJ, 2023)
The moral hazard problem in government organizations is very recurrent due to weak compensation system (i.e., take-home salary) and non-existence of any additional premium (e.g., ownership of stocks) for public policy makers compared to their counterparts in private firms, which weakens the proprietorship of their organization. Since there is a principal-agent relationship between citizens and public policymakers, a loss in public goods and services to citizens signals a meaningful level of moral hazard problem in public policymakers as agents. The menace of moral hazard problem can be lessened through a proper Reward Punishment Approach (RPA). Under existing setup, a weak compensation system with severe punishment mechanics indicates flaws in PRA which needs improvement through reforms in its existing structure. This paper focuses on bringing the compensation system (i.e., take-home salary in terms of cash and a provision of additional premium) at par with market-based package along with various perquisites. The study expects a bare minimum financial implication which may be affordable for the government and decrease moral hazard problem, at least to some extent, leading to a better delivery of public goods and services for the citizens of the country.